Nyadran Tradition as the Implementation of Religious Moderation in Buddhism - Andre Agustian Bagio; Wasantha Priyadarshana (Subhasita: Journal of Buddhist and Religious Studies, 2023)
The purpose of this study is to reveal the meaning and function contained in the nyadran ceremony in relation to religious moderation. The method used in this research is ethnography. The results of the research revealed that the Nyadran Kali tradition is a traditional activity carried out by the community. This tradition is carried out as an expression of gratitude to God and the ancestors for the blessings that have been received by the community in daily life, tradition is used as an activity as a means of creating harmony as a means of paying respect to ancestors. The Nyadran ceremony contains philosophical values related to the implementation of the delegation of services (pattidana) and to maintain the preservation of ancestral customs. There is an educational value considering the moderation in religion contained in the implementation of this tradition. That everyone can always develop a wise attitude or an attitude that has a strong belief in religion is very important, because a person can have the same right to be happy, the right to freely embrace the beliefs he holds and determine a peaceful and happy way of life, without causing suffering. for yourself and for others. Nyadran is an expression of gratitude to God or nature for being given the blessings of prosperity, fertility and abundant springs and the bestowing of services (Patidana), the cultivation of virtue (Dhana) and the implementation of religious moderation that can improve brotherly relations through preserving ancestral traditions (harmony between religious communities.